Activated FGFR3 prevents subchondral bone sclerosis during the development of osteoarthritis in transgenic mice with achondroplasia. Issue 1 (6th June 2017) - Okura, Toshiaki; Matsushita, Masaki; Mishima, Kenichi; Esaki, Ryusaku; Seki, Taisuke; Ishiguro, Naoki; Kitoh, Hiroshi
ABSTRACT: The purpose of this study is to investigate the morphometric changes of the subchondral bone during the development of osteoarthritis (OA) in transgenic mice with achondroplasia ( Fgfr3 ach ) carrying a heterozygous gain‐of‐function mutation in Fgfr3 . Two OA models (spontaneously developed with age: The aging model, and surgically induced by destabilization of the medial meniscus: The DMM model) were established. Articular cartilage, epiphysis, and metaphysis of the knee joint were histologically and morphometrically compared between wild‐type mice, and Fgfr3 ach mice in both OA models. Articular cartilage degeneration was scored according to the Osteoarthritis Research Society International (OARSI) scoring system. Several morphometric parameters including bone mineral density (BMD), bone volume/tissue volume (BV/TV), trabecular bone thickness (Tb.Th), and subchondral bone thickness in the medial tibial plateau (MTP) (Sb.Th med) were quantified by micro‐computed tomography (CT). In the aging model, although there were no significant differences in the OARSI score between wild‐type mice and Fgfr3 ach mice, Sb.Th med and Tb.Th in the epiphysis significantly increased in wild‐type mice. In the DMM model, the OARSI score of the medial compartment was significantly lower in Fgfr3 ach mice than in wild‐type mice. BMD, BV/TV, and Tb.Th in the epiphysis increased in wild‐type mice and unchanged in Fgfr3 ach mice, and the Sb.Th med was significantly larger in wild‐type mice after surgery. Subchondral sclerosis, which preceded the cartilage degeneration, was inhibited in Fgfr3 ach mice. Activated FGFR3 signaling prevented sclerotic changes of the subchondral bone and subsequent cartilage degeneration. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:300–308, 2018.